¿GRIEGO NEOTESTAMENTARIO Y TRADUCCIONES INTERESADAS? - Artés Hernández, José Antonio (Myrtia, 1997)
In the light of the Greek and Latin New Testament we reexamine some of the German theologian Uta Ranke’s most interesting points of view concerning, for example, Jesus’ supposed brothers and, generally speaking, women’s role in early christian communities. We infer from evidence of Greek canonical and apocryphal texts that some of her ideas could be finally accepted with a high level of certainty.